Assesment of Vegetation Cover Status in Dry Lands of The Sudan Using Social and Terrestrial Data - Mohammed Hamed Mohammed; Suzan Abdelrahman Hamad; Hassan Elnour Adam (Jurnal Ilmu Kehutanan, 2016)
The current study was conducted in 2015 in Bara Locality, North Kordofan, Sudan. The study area has experienced recurrent drought spells since 1970s of the past century. The main objective of this study was to assess and map the vegetation cover in the area using social, terrestrial and remotely sensed data. To accomplish the above mentioned objective, the study was based on qualitative and quantitative data. In qualitative data, household survey was conducted in which 100 respondents were randomly interviewed. Quantitative data was collected using terrestrial inventory and satellite imageries. In terrestrial inventory, 22 ground control points (GCPs) were randomly registered using GPS in order to get general overview of the land cover of the study area. In each GCP, tree species by number was inventoried within an area of 1 ha. Remote sensing data, covering the target study area, were acquainted using LANDSAT5 imageries (2014) with spatial resolution of 30×30 m. Results of the household survey revealed that only 13 shrub/tree species mentioned by 45% of the respondents, while only 9 woody species were identified, belonging to 8 families from terrestrial inventory. The results of the household survey, 45% of the respondents, indicated that vegetation cover was very good 20 years ago. The study categorized the present land cover as woody vegetation (19%), Acacia senegal stands (5%), shrubs i.e. Leptadenia pyrotechnica and Acacia nubica (18%), small scale farms and grasses (19%) and sandy soil and dunes (39%). The results of the land cover distribution indicated that vegetation cover decreased by 24% while sand/sand dunes was increased by 21% from 1985 to 2015. The study concluded that the study area is under threat of land degradation that may lead to depletion of vegetation cover and decline land productivity. Pengukuran Status Penutupan Vegetasi di Lahan Kering Sudan Menggunakan Data Sosial dan TerestrialIntisariPenelitian ini dilakukan pada tahun 2015 di Lokalitas Bara, Kordofan Utara, Sudan. Lokasi penelitian telah mengalami masa kekeringan yang berulang sejak dekade 1970-an. Tujuan utama dari penelitian ini adalah untuk menilai dan memetakan tutupan vegetasi di lokasi penelitian dengan menggunakan data sosial, terestrial, dan penginderaan jauh. Untuk mencapai tujuan dimaksud, penelitian ini menggunakan data kualitatif dan kuantitatif. Untuk data kualitatif, survei rumah tangga dengan wawancara terhadap 100 responden yang dipilih secara acak. Data kuantitatif dikumpulkan dengan menggunakan inventarisasi terestrial dan satelit citra. Untuk inventarisasi terestrial, 22 titik kontrol (GCP) didaftar secara acak dengan menggunakan GPS untuk mendapatkan gambaran umum dari tutupan lahan daerah penelitian. Pada setiap GCP, jumlah spesies pohon diinventarisasi dalam area 1 ha. Data penginderaan jauh yang mencakup wilayah studi diambil dengan citra LANDSAT5 (2014) dengan resolusi spasial 30 × 30 m. Hasil survei rumah tangga menunjukkan bahwa hanya 13 jenis semak/pohon yang disebutkan oleh 45% responden, sementara hanya 9 spesies kayu yang terindentifikasi, milik 8 keluarga dari inventarisasi terestrial. Berdasarkan hasil survei rumah tangga, 45% dari responden menyatakan bahwa tutupan vegetasi yang sangat baik 20 tahun yang lalu. Penelitian ini mengelompokkan tutupan lahan saat ini ke dalam vegetasi berkayu (19%), tegakan Acacia senegal (5%), semak yaitu Leptadenia pyrotechnica dan Acacia nubica (18%), pertanian skala kecil dan rerumputan (19%), dan tanah dan bukit pasir (39%). Hasil dari distribusi tutupan lahan menunjukkan bahwa tutupan vegetasi mengalami penurunan sebesar 24%, sedangkan proporsi pasir/bukit pasir meningkat 21% dari 1985 ke 2015. Penelitian ini menyimpulkan bahwa daerah penelitian berada di bawah ancaman degradasi lahan yang dapat menyebabkan penipisan vegetasi tutupan dan menurunkan produktivitas lahan.